Focused portfolios : a complete assessment for the young child - Gronlund, Gaye, 1952-; Engel, Bev, 1952- (Redleaf Press, 2019)
"Focused Portfolios, Second Edition offers an innovative method to accurately document children's growth and development by observing them in the midst of their everyday activities. This easy-to-use system has recently been updated to reflect current best practices in observation and assessment using portfolios, include information on apps and other digital tools to create portfolios, and incorporate individual state standards to develop portfolios that reflect the child's performance"--